Prevalence and identification of caprine pasteurellosis in pneumonic goats in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research aimed to assess the prevalence of caprine pasteurellosis, isolate and identify pasteurellosis (Mannheimia haemolytica and Pasteurella multocida) in pneumonic goats, and discover the main bacterial cause of pneumonia. Materials and Methods: One hundred and five samples (94 nasal swabs and 11 lung tissues) from goats suspected of having pneumonia were taken and transferred aseptically to the laboratory. Following the processing of the collected samples, Pasteurella spp. was isolated with the aid of plate culture methods. Biochemical characteristics were used to identify all bacterial isolates, which were then verified by polymerase chain reaction (PCR). Antimicrobial susceptibility testing was also carried out to evaluate the sensitivity profiles of various antibiotics. The Pasteurella haemolytica serotype-specific antigen (PHSSA) gene was used to identify isolates of M. haemolytica, and the KMT1 gene was used to identify isolates of P. multocida. Results: From the 105 clinically suspicious samples, 51 (48.57%) were identified to be Pasteurella spp. through bacteriological testing and also by PCR targeting the 16S rRNA gene. Of these, 47.87% (45/94) were nasal swabs, and 54.55% (6/11) were lung tissues. Among confirmed samples, 70.59% (36/51) were identified as M. haemolytica, and 29.41% (15/51) were identified as P. multocida. Resistance to tetracycline, streptomycin, oxytetracycline, gentamicin, and ceftriaxone was found in 50%–83% of the isolates. In addition, PCR identified the PHSSA and KMT1 genes from isolates of P. multocida and M. haemolytica, respectively. Conclusion: The present study revealed that M. haemolytica and P. multocida primarily caused pasteurellosis in pneumonic goats in Bangladesh. However, when treating these animals, the proper choice of antimicrobials should be made to control this disease.J. Adv. Vet. Anim. Res., 10(3): 538–544, September 2023http://doi.org/10.5455/javar.2023.j707